PENGARUH TINGKAT PERTUMBUHAN, STRUKTUR AKTIVA, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA SEKTOR PERTAMBANGAN - Dewi, Putu Ayu Ratih Purnama (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.07.TAHUN.2023, 2023)
Firm value reflects the present value of expected future earnings. Good financial management can maximize the value of the company. This study aims to determine the effect of growth rate, asset structure and firm size on firm value. The sample in this study is a mining company listed on the Indonesia Stock Exchange for the period 2018 – 2020. The sampling method used is a purposive sampling technique. By using several predetermined criteria, this study uses 30 mining companies. The data analysis technique used in this research is multiple linear regression analysis. The results in this study indicate that: The growth rate has no effect on the value of the mining companies listed on the IDX for the period 2018 - 2020. The asset structure has no effect on the value of the companies listed on the IDX for the period 2018 - 2020. The size of the company has no effect on company value in mining companies listed on the Indonesia Stock Exchange for the period 2018 - 2020. With this research, investors can be even more selective in choosing companies to invest in